1977
DOI: 10.1128/iai.15.2.417-422.1977
|View full text |Cite
|
Sign up to set email alerts
|

Selective response of lymphocytes from Treponema pallidum-infected rabbits to mitogens and Treponema reiteri

Abstract: The in vitro response of peripheral blood lymphocytes from rabbit infected with Treponema pallidum was examined using various mitogens and avirulent Treponema reiteri. For the first 4 weeks after treponemal infection, the response of lymphocytes from syphilitic rabbits to phytohemagglutinin and pokeweed mitogen was markedly reduced in comparison to uninfected controls. Lymphocytes from both groups of rabbits responded normally to class-specific immunoglobulin anti-sera (anti-immunoglobulin M and anti-immunoglo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
2

Year Published

1977
1977
1988
1988

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 19 publications
2
15
2
Order By: Relevance
“…Our data are not in agreement with those of Pavia et al (18)(19)(20), but precise reasons for the discrepancies are not clear. The kinetics and magnitude of the response to ConA in our study and in that of Bey et al (5) differ from those reported by Pavia et al (18)(19)(20); this may be related to differences in culture conditions. In our early attempts to optimize normal response, five lots of NRS were examined.…”
Section: Resultscontrasting
confidence: 99%
“…Our data are not in agreement with those of Pavia et al (18)(19)(20), but precise reasons for the discrepancies are not clear. The kinetics and magnitude of the response to ConA in our study and in that of Bey et al (5) differ from those reported by Pavia et al (18)(19)(20); this may be related to differences in culture conditions. In our early attempts to optimize normal response, five lots of NRS were examined.…”
Section: Resultscontrasting
confidence: 99%
“…Lymphocyte function is transiently impaired in the early phase of human syphilis as well as in experimental rabbit syphilis (8,11,12,14,(17)(18)(19)(27)(28)(29). Associated with this depressed lymphocyte responsiveness is the presence of an inhibitory factor in the blood of syphilitic humans (11,12) and rabbits (14,(17)(18)(19)(27)(28)(29). The factor(s) present in blood which is responsible for the lymphocyte hyporeactivity has not been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on experimental syphilis in rabbits have clearly established that the lymphocyte response to mitogens and T. pallidum is depressed during the first 3 to 4 weeks of the infection. In addition, a factor is present in the blood which inhibits the blastogenic response of lymphocytes from infected and uninfected rabbits (14,(17)(18)(19)(27)(28)(29).…”
mentioning
confidence: 99%
“…Plasma or serum from patients with the early stages of the disease was found to cause reduced levels of blastogenesis of normal lymphocytes (5,6). During the first few weeks of infection, lymphocytes from T. pallidum-infected rabbits respond poorly after being cultured with concanavalin A (12) or phytohemagglutinin and pokeweed mitogen (11). However, normal lymphoblastic responses were reached 5 to 6 weeks after initial infection in these animals.…”
Section: Discussionmentioning
confidence: 99%
“…In experimentally induced disease, a reduced number of lymphocytes was detected in the spleens of neonatal rabbits infected with T. pallidum (2). Poor in vitro responses to concanavalin A (12) and phytohemagglutinin and pokeweed mitogen (11) have been reported in T. pallidum-infected rabbits. In two studies with peripheral blood leukocytes in the migration inhibition test, inhibition of migration occurred only in the later stages of T. pallidum infection (4,20).…”
mentioning
confidence: 99%